Dynamics of Wives' Social Role Adaptation in Marriage: A Phenomenological Study on Identity Negotiation and Harmony from the Perspective of Islamic Family Law - Abdurrahman Arrafi; Muhsan Syarafudin (Journal Analytica Islamica, 2026)
Islamic marriage aims to manifest a sakinah family, yet high divorce rates and contemporary gamophobia phenomena necessitate a new understanding of relational resilience. This phenomenological study explores wives' subjective experiences in character adaptation and highlights its novelty in reinterpreting the concept of qiwamah (husband's leadership) and family harmony in contemporary marriage. Through in-depth interviews with six female informants, this study found that character adaptation is not passive submission, but an active and dialogical identity negotiation strategy. The novelty of this article lies in the finding that wives' subjective experiences directly deconstruct rigid textual understandings; qiwamah is no longer interpreted as absolute patriarchal dominance but reinterpreted as an egalitarian consultative mechanism to achieve harmony. In conclusion, Islamic Family Law texts are practically operating as a flexible living law. The main contribution of this research theoretically offers a new paradigm of egalitarian husband-wife power relations, and practically recommends the revitalization of pre-marital guidance at the Office of Religious Affairs (KUA) focusing on conflict resolution and role negotiation.